HARMONY OF THE PHILOSOPHICAL FOUNDATION OF ENGLISH TEXTBOOKS AND THE 2013 ENGLISH CURRICULUM - Sugianti, Lilik; Purwati, Oikurema; Setiawan, Slamet; Anam, Syafi'ul (Universitas Muhammadiyah Metro, 2022)
Philosophy is one of the most important fundamental aspects in developing the 2013 curriculum to determine teaching and learning objectives and processes. Accordingly, textbooks should represent curriculum ideas. It must be developed in line with the philosophical foundation of the curriculum. It is to realize the objectives of teaching and learning that emphasize critical thinking and student character development. This study aimed to reveal the philosophical foundations of LKS (Lembar Kerja Siswa) in English ninth grade and its compatibility with the 2013 curriculum. LKS is an exercise guide for developing cognitive aspects and all learning aspects in the form of an experimental or demonstration guide. This study used inferential content analysis on six units of LKS-English in ninth grade, semester one, publisher by CV. Library Pillar. It examined six philosophical foundations in LKS-English of ninth grade: existentialism, essentialism, perennials, humanism, social reconstruction, and progressivism. It also examines six philosophical foundations in the 2013 curriculum, including essentialism, perennials, humanism, social reconstruction, progressivism, and idealism. So, there is a harmony between the philosophical foundation of the LKS-English of ninth grade and the 2013 Curriculum. The LKS-English and the 2013 curriculum focus on developing students' character and 21st-century skills, such as critical thinking, problem-solving, communication, collaboration, creativity, and innovation.